Innovative Learning Video: Combination of Basic Locomotor Movement Patterns for First Grade Elementary Students - Wijaya, I Wayan Aditya Kurnia; Putrayasa, Ida Bagus; Sudiana, I Nyoman (Jurnal Pedagogi dan Pembelajaran, 2024)
The lack of student learning development in physical education, sports, and health (PJOK) learning materials is a challenge for educators to improve students' learning understanding. This study aims to develop PJOK learning video media in the material of basic locomotor movement combinations for grade I elementary school students. This study is a development research (R&D) using the ADDIE model. The subjects of the study were grade I elementary school students. Data were obtained through non-test techniques to obtain data on the validity and practicality of the product and test methods for product effectiveness. Data were analyzed with percentages for validity and practicality tests, while effectiveness tests were carried out using a t-test burning with a one group pretest-posttest design. The results showed that the PJOK learning video material on the combination of basic locomotor movement patterns was declared very valid, practical with very good qualifications, and effective in improving students' understanding of locomotor movements. Based on these results, it was concluded that the innovation of PJOK learning videos on the combination of basic locomotor movement patterns was declared feasible as a learning resource and effective. This study has implications for improving elementary school students' understanding of basic locomotor movement combinations.